Comprehensive analysis of targetable mutations and tumor microenvironment in urachal cancer - David J. Benjamin; Tolulope T. Adeyelu; Andrew Elliott; Sourat Darabi; Thomas Lee; Rana R. McKay; Matthew J. Oberley; Arash Rezazadeh Kalebasty (npj Precision Oncology)
Abstract Urachal cancer, a rare malignancy, generally presents in the clinical setting with advanced stages of disease. Systemic treatment with chemotherapy is generally utilized in this setting. However, there remains a paucity of data on the effectiveness of immune checkpoint inhibitors or targeted therapies for urachal cancer. We analyzed the genomic profile of urachal cancer in order to identify potentially targetable mutations and evaluate the tumor microenvironment. 42 urachal samples were retrospectively analyzed. Our results showed that TP53, GNAS and KRAS mutations were common in urachal cancer with increased prevalence of TP53 mutation in urachal cohorts without MAPK-alterations. The tumor microenvironment demonstrated increased NK cells in MAPK-altered urachal cancer. Finally, we show that urachal cancer shares genomic and transcriptomic similarity with colorectal cancer compared to bladder cancer. This study provides new insights into the molecular profiles of urachal tumor samples and possibility of association with colorectal cancer that might guide future clinical trial design.